Penguatan Budaya Literasi Digital Melalui Praktik Baik Pembuatan Poster untuk Mencegah Cyber Bullying bagi Siswa Madrasah Aliyah Al-Maarif Singosari Malang - Nudya Kuntum Khoirel Abidah; Trisna Andarwulan; Very Erawanto; Ahmad Daril Atfal; Aisyah Cahya Ramadhani; Angela Fransisca Sabrina Panggabean; Kamila Zahra Hapsari; Muthia Jihan Alvina (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The use of the internet by Indonesian students has become increasingly significant due to the advancement of information and communication technology. Indonesia has approximately 196.7 million active internet users, with 22% of them being 19 years old or younger. To effectively interact with and process digital information from various media, it is crucial for students to possess digital literacy skills. These skills are essential for adolescents' social interactions to mitigate the negative impacts of lacking skills, security protection, and digital ethics, such as fake news and cyberbullying. To address this, the MA Al-Maarif Singosari environment aims to aid and promote a digital literacy culture. This includes socializing the four pillars of digital literacy and reinforcing these skills through creating educational posters, which are grammatically correct, use appropriate vocabulary, and feature attractive and relevant illustrations. Feedback and coaching are also provided to improve the posters. As a result of this service, participants can improve digital literacy culture by making good practices for making cyber bullying prevention posters that can increase participants' awareness to be ethical and cultured while using digital media, so that digitally proficient but still humane humans are formed who can improve the quality of education and eradicate cyber bullying in the school environment.